A new and distinctive species of the hermit crab genus Catapaguropsis (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea - Mclaughlin, Patsy A.; Lemaitre, Rafael (Zootaxa, 2007)
The diagnosis of the recently described hermit crab genus Catapaguropsis Lemaitre & McLaughlin, 2006 is emended to accommodate a second distinctive new species, Catapaguropsis brucei n. sp., which does not exhibit the sexual dimorphism described for the type species, C. queenslandica Lemaitre & McLaughlin, 2006. Catapaguropsis brucei n. sp. is characterized by the marked reduction, in both sexes, of the posterior portions of the pleons, uropods, and telsons that are encased by cnidarians. In addition to the description and illustrations, this new species is compared and contrasted with species of other pagurid genera that occupy atypical carcinoecia.